Students Critical Thinking Skills in Project-Based Learning Assisted by Edmodo Social Networking Site - Rosiyanah, Siti; Wijayati, Nanik; Masturi, Masturi (Postgraduate, Universitas Negeri Semarang, Indonesia, 2019)
The project-based learning model developed by collaborating with the social networking site Edmodo is expected to be able to change the educational paradigm which once embraced teacher-centered learning into student-centered learning. This study aims to determine the effectiveness of project-based learning model assisted by Edmodo’s social networking site on critical thinking skills and student learning outcomes. This research was conducted in class VIII SMP Negeri 6 Jepara in even semester of Lesson 2018/2019 year on substance pressure. The research design used was pre-test and post-test control group design. The data were collected by questionnaire, observation, documentation and test method. The results showed that the value of tcount  critical thinking skills and student learning outcomes > ttable value (2.042). The value of tcount critical thinking skills and learning outcomes respectively is 12.714 and 2.757. The results of this study conclude that the project-based learning model assisted by Edmodo's social networking site is effective to improve critical thinking skills and student learning outcomes.